COGNITIVE VIEW OF LEARNING - Liqa Fadhila; Neviyarni; Herman Nirwana (Yayasan Citra Dharma Cindekia, 2021)
Learning is a process that an individual experiences from time to time. During the learning process, students have different characteristics and learning methods. To maximize the learning process, many learning theories that can be applied later to understand and support the student's learning process are created. One of them is Jean Piaget's cognitive learning theory. The cognitive view of learning assumes that the most important thing in learning is not only the result but also the process. . Cognitive learning theory focuses on examining individual differences to assist in the interpretation of learning outcomes. Cognitive psychologists have used a much wider range of research methods to study learning. This includes ways students need to explain their mental processes during learning.